THE MASSIVE STELLAR POPULATION IN THE DWARF STARBURST GALAXIES - Guseva, N. G. (Одеські астрономічні публікації, 2017)
The analysis of the long-slit spectral observations of 39 Wolf-Rayet (WR) galaxies with heavy element mass fraction ranging over 2 orders of magnitudes from Z☉/50 to 2Z☉ are presented. We derive the number of O stars from the luminosity of the Hβ emission line, the number of early carbon Wolf-Rayet stars (WCE) from the luminosity of the red bump (broad CIV Λ5808 emission) and the number of late nitrogen Wolf-Rayet stars (WNL) from the luminosity of the blue bump (broad emission near Λ 4650). We identified some of weak WR emission lines, most often the N III Λ 4512 and Si III Λ 4565 lines, which have very rarely or never been seen and discussed before in WR galaxies. A new technique for deriving the number of WNL stars (WN7-WN8) from the N III Λ 4512 and the number of WN9-WN11 from Si III Λ4565 emission lines has been proposed. This technique is potentially more precise than the blue bump method because it does not suffer from contamination of WCE and early WN (WNE) stars and nebular gaseous emission. We find that the fraction of WR stars relative to all massive stars increases with increasing metallicity, in agreement with predictions of evolutionary synthesis models. The relative number ratios N(WC)/N(WN) and the equivalent widths of the blue and red bumps derived from observations are also in satisfactory agreement with theoretical predictions, except for the most metal-deficient WR galaxies. A possible source of disagreement is too low a line emission luminosity adopted for a single WCE star in low-metallicity models.